1997
DOI: 10.1177/004051759706700208
|View full text |Cite
|
Sign up to set email alerts
|

Compression and Packing Density of Fibrous Assemblies

Abstract: This paper presents a generalization of the unidimensional deformation equation based on the van Wyk theory. The derivation considers the effect of uncompressed areas between contacting fibers. Theoretical results are verified by the experimental work of Baljasov. The solution is extended to cover bidimensional deformation of an oriented fibrous assembly. The work also proves the importance of using fiber packing density as the argument in the compression equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…There are numerous mechanistic models developed based on response of the fibers at the micro-level, but none of them are suitable for studying macro-level compression behavior of felt. Stamm [5] showed that the micromechanical approaches developed by van Wyk [6], Neckář et al [7], and Komori et al [8,9] failed to match experimental results for felt compression. Furthermore, Masoudi [3] utilized a more sophisticated model proposed by Alkhagen et al [10], which was based on a constitutive relation for a fiber mass using the rate theory of flexible granular solids, but unsatisfactory results were obtained for compression of felt with various volume fractions.…”
Section: Micromechanics Of Random Fiber Network Including Hysteresismentioning
confidence: 99%
“…There are numerous mechanistic models developed based on response of the fibers at the micro-level, but none of them are suitable for studying macro-level compression behavior of felt. Stamm [5] showed that the micromechanical approaches developed by van Wyk [6], Neckář et al [7], and Komori et al [8,9] failed to match experimental results for felt compression. Furthermore, Masoudi [3] utilized a more sophisticated model proposed by Alkhagen et al [10], which was based on a constitutive relation for a fiber mass using the rate theory of flexible granular solids, but unsatisfactory results were obtained for compression of felt with various volume fractions.…”
Section: Micromechanics Of Random Fiber Network Including Hysteresismentioning
confidence: 99%
“…ProTkaTex enables 3D visualization of fabrics based on the input yarn parameters. It is used for properties, prediction on the basis of combination of mathematical modeling and experimental research [2,4,31]. The major challenge is to develop a software package that industry will use in design centers for the creation and development of new fabric structures for technical as well as clothing application.…”
Section: Prediction Of Woven Fabric Properties: Software Protkatexmentioning
confidence: 99%
“…As mentioned above, the software calculates selected properties for dobby as well as jacquard woven fabric. It is possible to predict the following properties of fabrics: relative is dependent on the yarn structure and fabric input parameters (weave, warp and weft waviness, warp and weft sett) [4,33]. In the following model (1), the main infl uence is from yarn diameter and weft and warp waviness.…”
Section: Weave Defi Nition and Prediction Of Woven Fabric Propertiesmentioning
confidence: 99%
See 2 more Smart Citations